Modeling and analysis of Cloud-P2P storage architecture - Shun-fu JIN; Chen-fei WANG; Ling-ling CHEN; Zhan-qiang HUO (Tongxin xuebao)
Based on the Cloud-P2P storage architecture, taking into account the data access mechanism with both the data center and the peer-based layer, considering the repair process of the replica, a three-dimensional Markov chain model was constructed. The steady-state analysis of the model is obtained by using a matrix-geometric method. Then, the per-formance measures in terms of peer-based traffic load, the average access time, and the repair rate are given. Moreover, numerical results with analysis and simulation are provided to demonstrate the influence of the system parameters on the system performance. By constructing a benefit function, the number of replicas in peer-based layer is optimized.